2020
DOI: 10.21203/rs.2.21269/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The incremental prognostic value of sIL-2R and HGF in acute ischemic stroke

Abstract: Background: Inflammation affect long-term neurological outcome after acute ischemic stroke (AIS). Comprehensive and insightful understanding of correlation of inflammatory mediators and stroke outcome may offer new biomarkers or therapeutic approaches for AIS. Methods: We collected plasma from 204 AIS patients and 76 healthy controls, and ten cytokines (HGF, IL-1β, IL-2, sIL-2R, IL-5, IL-10, IL-16, MIP-3α, CD40L and MMP1) screened out by Immune Monitoring 65-Plex Human ProcartaPlex Panel were measured. Functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…They explained it by its pathological role in plaque progression and instability and greater degree of baseline endothelial dysfunction [20] with subsequent infarct expansion and hemorrhagic transformation [31]. This conclusion was supported by recent study by Zhao and colleagues; they found that soluble interleukin-2 receptors (sIL-2R) and HGF associated with unfavorable outcomes at 3 months after acute ischemic stroke [32].…”
Section: Severity Of Atherosclerosis K Test (P Value)mentioning
confidence: 82%
“…They explained it by its pathological role in plaque progression and instability and greater degree of baseline endothelial dysfunction [20] with subsequent infarct expansion and hemorrhagic transformation [31]. This conclusion was supported by recent study by Zhao and colleagues; they found that soluble interleukin-2 receptors (sIL-2R) and HGF associated with unfavorable outcomes at 3 months after acute ischemic stroke [32].…”
Section: Severity Of Atherosclerosis K Test (P Value)mentioning
confidence: 82%